Stirling's Engine (Texas Journal of Multidisciplinary Studies, 2022)
The internal combustion engine has supplanted other types of power plants, however, work aimed at abandoning the use of these units suggests an imminent change in leading positions. Since the beginning of technological progress, when the use of engines that burn fuel inside was just beginning, their superiority was not obvious. The steam engine, as a competitor, contains a lot of advantages: along with traction parameters, it is silent, omnivorous, easy to control and configure [1-2]. But lightness, reliability and efficiency allowed the internal combustion engine to take over the steam